Free Game Education Assessment Development "Button Go Green" on Green Chemical Materials - Meydia Afrina; Syukri Hamzah; Hadiwinarto Hadiwinarto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Green chemistry is material in class X in the driving school curriculum. This material is very closely related to phenomena in everyday life. For that, we need an interesting and meaningful assessment in the form of games that are easy to use. This study aims to determine the feasibility of the "Go Green" education game-based assessment on green chemistry, determine the characteristics of the game education-based assessment and determine the effectiveness of the "Go Green" education game assessment on green chemistry. The research and development method used was adapted from the ADDIE model which consists of five stages, namely Analysis, Design, Develop, Implementation, Evaluation. The research subjects were students of class X SMA Negeri 9 Bengkuku Selatan. The instruments used are questionnaires and quantitative descriptive data analysis. The results showed that material expert validation was 93.42% and media expert validation was 92.86% with a feasible category for implementation. Based on the results of the development carried out, it can be concluded that the assessment developed has met the appropriate criteria. "Go Green" can help educators in conducting assessments effectively and optimally and make students relax in doing questions well.